System of the complicated practical problems analysis - Kolesnikov, A. V.; Fedorov, O. P. (Mathematical Modelling and Analysis, 2002)
The original methodology of the system analysis of the inhomogeneous problem is offered, including stages of its reducing to homogeneous parts and selecting for them appropriate toolkits: methods and models. This system applies the accumulated knowledge and the experts skills to refer of each homogeneous problem to one or several alternative classes of modelling methods: analytical methods, statistical methods, artificial neuronets, knowledge based systems, fuzzy systems, genetic algorithms. The knowledge base testing has shown sufficiency and consistency of knowledge for realization of the inhomogeneous problems analysis even in conditions with a low and average distortion in the problem descriptions. Sudėtingų praktinių uždavinių sistemos analizė Santrauka. Pasiūlyta nehomogeninio uždavinio sisteminės analizės originali metodika. Ji apima redukcijos į homogenines dalis etapus, parenka atitinkamus metodus ir modelius. Sukauptos teorinės žinios ir ekspertų įgūdžiai pritaikomi priskiriant kiekvieną homogeninį uždavinį vienai arba kelioms modeliavimo metodų alternatyvioms klasėms. Teorinių žinių testavimas duoda pakankamą ir nuoseklią analizę realizuojant nehomogenines sistemas, esant mažiems ir vidutiniams netikslumams problemos apibūdinime. First Published Online: 14 Oct 2010